Outsourcing Moral Authority: The Internal Secularization of Evangelicals' Anti-Pornography Narratives - Thomas, Jeremy N. (Journal for the scientific study of religion, 2013)
Based on content analysis of the popular evangelical magazine Christianity Today, I show that while evangelicals' outward opposition to pornography has remained steady and robust across the period 1956 to 2010, nonetheless, during this same time, evangelicals' anti-pornography narratives have become increasingly secular. Through using and expanding Chaves's notion of internal secularization, I demonstrate how these narratives have become decreasingly legitimated through religious forms of moral authority such as scriptural prohibitions and derivative ideas about God's plan for society, and increasingly legitimated through secular forms of moral authority such as humanistic conceptions of individual rights and of psychological health. I refer to this type of internal secularization as the process of outsourcing moral authority, and I discuss the theoretical significance of this process for potential investigations of a range of other moral narratives.